Ruqyah as a Therapeutic Communication Media - ., Khairullah; ., Faizal; Makmun, Fariza (Universitas Islam Negeri Raden Intan Lampung, 2023)
This article discusses the reality of Muslims and how they perceive the Qur’an by using certain verses in the practice of ruqyah. The functionalization of Al-Qur'an verses in the practice of ruqyah, which is carried out jointly between the raqi and the client, is a therapeutic communication medium. It is the Ruqyah Quar'anic Healing International (QHI) Institute in the Lampung Region, which, in practice, uses verses from the Qur’an as a means of curing clients' illnesses. This research uses a qualitative approach using primary and secondary data sources explored using snowball sampling. Based on the interviews and observations, data was found that the reception of the Qur’an through the practice of ruqyah can be said to be a therapeutic communication medium. Second, raqi, as communicators and clients as communicants, understand ruqyah as a form of receiving the Qur’an, which is believed to have supernatural powers that can cure psychological and physical illnesses. Third, from a da'wah perspective, in the mass ruqyah process, a social network is built between raqi and clients. Fourth, the practice of receiving the Qur'an in the ruqyah process can help individuals who are obedient to Allah SWT to form.